Prevalence and factors associated with high risk for obstructive sleep apnea in schizophrenia spectrum disorder patients on long-term clozapine - Rika Rijal; Sandeep Grover; Subho Chakrabarti; Swapnajeet Sahoo (Indian Journal of Psychiatry)
Aim: This study aimed to evaluate the prevalence of obstructive sleep apnea (OSA) and its correlates among schizophrenia spectrum disorder patients receiving clozapine. Methods: For this, 200 schizophrenia spectrum disorder patients receiving clozapine for at least one year were assessed on the Berlin Sleep Questionnaire for OSA. Results: Around one-sixth of the study sample (16.5%) had a high risk for OSA at a body mass index (BMI) cut-off of 30 kg/m2. When a BMI cut-off of 25 kg/m2 was used, the prevalence of OSA was 36%. A high risk for OSA is associated with a higher prevalence of depression, a higher number of psychiatric comorbidities, diabetes mellitus, a higher mean total chlorpromazine equivalent dose, a higher number of total medications, poorer quality of life in some of the domains, and scored high for all domains and the total score of UKU. Conclusion: To conclude, this study suggests that a high risk of OSA is associated with the presence of depression, a higher number of psychiatric comorbidities, diabetes mellitus, use of higher total chlorpromazine equivalent dose, the total number of medications, poorer quality of life, and a higher prevalence of other side effects.